Real-world experience with elective discontinuation of PD-1 inhibitors at 1 year in patients with metastatic melanoma. Issue 1 (26th January 2021) - Pokorny, Rebecca; McPherson, Jordan P; Haaland, Benjamin; Grossmann, Kenneth F; Luckett, Carolyn; Voorhies, Benjamin Newell; Sageser, Daniel S; Wallentine, Jocelyn; Tolman, Zachary; Hu-Lieskovan, Siwen; Swami, Umang
Abstract : Background: Randomized trials evaluating programmed cell death protein 1 (PD-1) inhibitors in metastatic melanoma either permitted treatment for 2 years (pembrolizumab) or more (nivolumab). The optimal duration of therapy is currently unknown due to limited data, and shorter therapies may be effective. Methods: Data of patients with metastatic cutaneous melanoma treated with single-agent PD-1 inhibitors at Huntsman Cancer Institute from January 1, 2015, to December 31, 2018, was reviewed to identify a continuous series of patients who made the joint decision with their provider to electively discontinue therapy at 1 year (>6 months and <18 months) in the setting of ongoing treatment response or disease stability. Patients were excluded if they received PD-1 inhibitors with other systemic therapy, had prior exposure to PD-1 therapy, or discontinued treatment due to disease progression or immune-related adverse event. Best objective response (BOR) per RECIST V.1.1 at treatment discontinuation, progression-free survival (PFS), and retreatment characteristics was analyzed. Results: Of 480 patients who received PD-1 inhibitors, 52 met the inclusion criteria. The median treatment duration from first to the last dose was 11.1 months (95% CI 10.5 to 11.4). BOR was complete response in 13 (25%), partial response in 28 (53.8%), and stable disease in 11 (21.2%) patients. After a median follow-up of 20.5 months (range 3–49.2) from treatment discontinuation, 39 (75%) patients remained without disease progression, while 13 (25%) had progression (median PFS 3.9 months; range 0.7–30.9). On multivariable analysis, younger age, history of brain metastasis, and higher lactate dehydrogenase at the time of anti-PD-1 discontinuation were associated with recurrence. Patients with recurrent melanoma were managed with localized treatment, anti-PD-1 therapies, and BRAF-MEK inhibitors. All patients except one were alive at data cutoff. Conclusion: In this large real-world, observational cohort study, the majority of patients with metastatic melanoma after 1 year of anti-PD-1 therapy remained without progression on long-term follow-up. The risk of disease progression even in patients with residual disease on imaging was low. After prospective validation, elective PD-1 discontinuation at 1 year may reduce financial and immunotherapy-related toxicity without sacrificing outcomes.